Low-input dairy farming in Europe: Exploring a context-specific notion. (September 2017) - Bijttebier, J.; Hamerlinck, J.; Moakes, S.; Scollan, N.; Van Meensel, J.; Lauwers, L.
Abstract: Frequently acknowledged as coming forward to environmental issues by reducing external input use, low input (LI) dairy farming is gaining attention. The absence of a clearly delineated description of LI dairying, however, hampers identification and analysis of these farming systems. This paper aims at empirically examining, EU wide, the farm structure, production intensity and productivity of LI with respect to their high input (HI) conventional counterpart and to organic dairying (ORG). A pragmatic quartiles-based categorization of farms from the Farm Accountancy Data Network of 20 important EU dairy countries, with the value of external input costs per grazing livestock unit (GLU) is used as prior discriminating indicator between LI and HI. LI dairy farms are smaller than HI dairy farms, in particular when farm size is expressed as total farm capital. Other variables that differentiate between LI and HI in most countries are number of dairy cows per GLU and area of forage and grassland on total agricultural area. Partial productivities in HI farms exceed those in LI farms, most apparent is milk production per cow. Differentiation of forage production between LI and HI is less uniform throughout Europe. A pairwise matching of differentiation profiles between countries indicates that differentiation between LI and HI is country specific. A similar diversity in country-specific differentiation between ORG and LI farming is found. Highlights: Increased interest in low input farming Different motivations and strategies behind reduced external input use provide difficulties to identify these farms Proposition of a quartiles-based categorization of farms based on external input use intensity at the whole farm level Profiling analysis of dairy farms across Europe according to their input use Differentiation profiles of high and low input farms are country specific